AGRONOMIC AND GRAIN YIELD TRAITS OF RICE VARIETIES UNDER SEASONAL VARIATION IN TROPICAL LOWLANDS - Muhammad Muharram; Agus Suryanto; Sudiarso; Anna Satyana Karyawati (SEAMEO BIOTROP, 2026)
ARTICLE HIGHLIGHTS- Planting time in the wet season changed rice growth and grain yield.- Mid rainy season planting reduced grain yield in all tested rice varieties.- Hybrid Intani 602 recorded the highest yield in late rainy season planting.- Grain yield increased with greater plant biomass and faster crop growth.- Longer flowering and maturity were associated with lower grain yield.ABSTRACTRice (Oryza sativa L.) is a strategic crop in Southeast Asia, where seasonal variation strongly influences its growth, physiology, and yield. This study evaluated the agronomic performance and yield components of three rice genotypes representing local (Pandan Wangi), improved (Inpari 32), and hybrid (Intani 602) types across three planting periods within the wet season (early, mid, and late rainy season) in tropical lowland fields of East Java, Indonesia, during 2023 – 2024. The experiment was arranged in a randomized complete block design within each planting period, and data were analyzed using combined ANOVA, correlation analysis, and genotype by trait (GT) biplot. Results indicated that genotype and planting period significantly affected most agronomic and yield traits, with significant genotype × planting period interactions observed for several key variables. Grain yield was positively associated with biomass accumulation and growth efficiency (DW and CGR) and supported by canopy development (LAI), whereas phenological duration (DTF and DTM) showed negative associations with yield under the tested wet season conditions. GT biplot analysis explained 77.95% of the total variation (PC1 = 64.48%, PC2 = 13.47%) and indicated that hybrid combinations in the late rainy season planting period were closely associated with major yield and biomass traits, while Inpari 32 in the early rainy season planting period was more closely associated with radiation use indices (EPA and RUE) and tiller related traits. Pandan Wangi combinations were positioned nearer to phenological and vegetative traits with lower yield levels. Overall, the findings provide a site-specific basis to interpret varietal suitability and planting period sensitivity within the wet season in tropical lowland rice systems.